WE THINK THE BAROQUE OF MINEIRO, WE FIND EUCLIDIAN GEOMETRY - Anna Sapunaru, Raquel; Frederico Guimarães Santiago, Douglas (Journal of Interdisciplinary Debates, 2023)
Despite the Baroque presenting itself as the movement of the human soul, which proposes to break definitively with the rigidity of the Classic, we observe the permanence of Euclidean Geometry in several details of the Baroque churches of Diamantina. In this way, we rescued a little of the history of the Baroque, while mathematically investigating some observed details, thus finding the Classic in the Baroque.